Barriers and Opportunities of Canyoning in Nepal - Gautam, Susmita (NUTA Journal, 2023)
Adventure tourism is main category of the tourism in Nepal and source of National economy. It is multidimensional and multidisciplinary in terms of nature itself and closely with culture and increase to per capita income. To know about the prospect and probability of the adventure tourism based on canyoning in Lamjung is the general objective of this study. Lamjung's continuous tourism activities are hindered by poorly implemented adventure tourism, affecting the environment, and promoting sustainable and beneficial industries for locals. So, this study tried to explore minutely the adventure canyoning aspects consistency with degradation in study area. A mixed method approach was used, involving primary and secondary data from canyoning companies, local guides, and experienced clients whereas required data collected using structured questionnaire, KII and FGD. The data was analyzed quantitatively and qualitatively. The study aimed to identify the causes and hidden facts of the degradation of Adventure Canyoning. Therefore, this study holds significant social science importance as it aims to reduce issues related to adventure canyoning in the study area. The study reveals that sustainable practices and responsible tourism can contribute to the long-term viability of canyoning as an adventure sport.